1998
DOI: 10.1016/s0092-8674(00)81223-4
|View full text |Cite
|
Sign up to set email alerts
|

Hsp104, Hsp70, and Hsp40

Abstract: Hsp104 is a stress tolerance factor that promotes the reactivation of heat-damaged proteins in yeast by an unknown mechanism. Herein, we demonstrate that Hsp104 functions in this process directly. Unlike other chaperones, Hsp104 does not prevent the aggregation of denatured proteins. However, in concert with Hsp40 and Hsp70, Hsp104 can reactivate proteins that have been denatured and allowed to aggregate, substrates refractory to the action of other chaperones. Hsp104 cooperates with the chaperones present in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

33
601
0
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,282 publications
(638 citation statements)
references
References 49 publications
33
601
0
4
Order By: Relevance
“…The phenomenon of disaggregation was first reported in S. cerevisiae where heat denatured proteins can be efficiently reactivated by the cooperative action of Hsp70-Hsp40 and the oligomeric, ring forming AAA+ ATPase chaperone Hsp104 (Glover and Lindquist, 1998;Parsell et al, 1994). Soon after the discovery of Hsp104 disaggregase in yeast, an orthologous protein called ClpB was shown to possess disaggregation activity in E. coli and in chloroplasts and mitochondria of higher eukaryotes .…”
Section: Ii441 Chaperone Mediated Refolding and Disaggregationmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenomenon of disaggregation was first reported in S. cerevisiae where heat denatured proteins can be efficiently reactivated by the cooperative action of Hsp70-Hsp40 and the oligomeric, ring forming AAA+ ATPase chaperone Hsp104 (Glover and Lindquist, 1998;Parsell et al, 1994). Soon after the discovery of Hsp104 disaggregase in yeast, an orthologous protein called ClpB was shown to possess disaggregation activity in E. coli and in chloroplasts and mitochondria of higher eukaryotes .…”
Section: Ii441 Chaperone Mediated Refolding and Disaggregationmentioning
confidence: 99%
“…Soon after the discovery of Hsp104 disaggregase in yeast, an orthologous protein called ClpB was shown to possess disaggregation activity in E. coli and in chloroplasts and mitochondria of higher eukaryotes . Several in vitro studies have shown that the Hsp104 or ClpB system alone has little or no disaggregation activity and requires collaboration with the Hsp70 system for effective disaggregation (Glover and Lindquist, 1998;Goloubinoff et al, 1999).…”
Section: Ii441 Chaperone Mediated Refolding and Disaggregationmentioning
confidence: 99%
“…Hsp16.9, Hsp17.1, Hsp17.3 and Hsp18.1 are shown to prevent the aggregation or denaturation of proteins during HS (Lee et al, 1995;Yeh et al, 1997;Young et al, 1999;Low et al, 2000). Hsp100 is shown to rescue the heat-induced protein aggregates by their re-solubilization during the recovery phase (Glover and Lindquist, 1998). Certain other Hsps such as Hsp40, Hsp60, Hsp70 and Hsp90 (alone or in co-operation) stabilize the heat-denatured proteins (Hartl et al, 1994;Glover and Lindquist, 1998;Buchner, 1999).…”
Section: Synthesis To Propose a Modelmentioning
confidence: 99%
“…Hsp100 is shown to rescue the heat-induced protein aggregates by their re-solubilization during the recovery phase (Glover and Lindquist, 1998). Certain other Hsps such as Hsp40, Hsp60, Hsp70 and Hsp90 (alone or in co-operation) stabilize the heat-denatured proteins (Hartl et al, 1994;Glover and Lindquist, 1998;Buchner, 1999). Detailed studies in model systems like Arabidopsis, yeast and human cell lines show that several different Hsps act in synchronous manner to prevent aggregation or re-fold the aggregated proteins.…”
Section: Synthesis To Propose a Modelmentioning
confidence: 99%
“…The result is unfolding and aggregation of various cellular proteins [ 7 ], activation of the stress genes [ 8 ] and heat shock proteins (Hsps) synthesis. The concentration of proteins, products of these genes, is increased in response to stressors, thus protecting the cells from the damaging effects of stress and accelerating recovery by helping renaturation of partially-denaturated proteins [ 9 ].…”
mentioning
confidence: 99%